2017
DOI: 10.1007/s00405-017-4557-0
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic differences between conventional and follicular variant papillary thyroid carcinoma

Abstract: Follicular variant papillary thyroid carcinoma (FVPTC) may pose a diagnostic challenge due to higher likelihood of lower risk cytology compared to conventional papillary thyroid carcinoma (CPTC). Recent guidelines have recommended the use of sonographic features to guide decisions to biopsy thyroid nodules. The purpose of this study was to evaluate the sonographic features of CPTC and FVPTC. This is a retrospective study design done in an Academic teaching hospital setting. Preoperative ultrasounds of 79 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Invasive encapsulated FV is typically a hypoechoic lesion with rather smooth margins and no calcifications. Nodule shape, orientation, and vascularity are similar to the infiltrative type of FV [31,39]. Similar observations concerning more benign US features of nodules harboring RAS mutations were presented by Rossi et al [25], who demonstrated that most of them were isoechoic.…”
Section: Genetic Drivers and Sonographic Pattern Of Different Varisupporting
confidence: 56%
See 2 more Smart Citations
“…Invasive encapsulated FV is typically a hypoechoic lesion with rather smooth margins and no calcifications. Nodule shape, orientation, and vascularity are similar to the infiltrative type of FV [31,39]. Similar observations concerning more benign US features of nodules harboring RAS mutations were presented by Rossi et al [25], who demonstrated that most of them were isoechoic.…”
Section: Genetic Drivers and Sonographic Pattern Of Different Varisupporting
confidence: 56%
“…BRAF K601E mutations are present in most cases of the infiltrative follicular variant (FV) [12]. In US, these nodules are often hypoechoic, with spiculated/microlobulated margins and microcalcifications [31,39]. The differences in the US pattern of FV PTC depending on genetic drivers are discussed further below.…”
Section: Genetic Drivers and Sonographic Pattern Of Different Varimentioning
confidence: 99%
See 1 more Smart Citation
“…This would be expected, as established suspicious US features are suggestive of this cancer type 2 . All of the misclassified cancers by radiologists were either FVPTC or minimally invasive follicular thyroid carcinoma, which tend to show more benign US features 29,30 . Although sCAD and dCAD showed a similar number of misclassified cancers, they differed in characteristics – conventional papillary thyroid carcinoma accounted for 72.7% (8 of 11) of the misclassified cancers by sCAD, whereas it accounted for only 33.3% (4 of 12) of the misclassified cancers by dCAD.…”
Section: Discussionmentioning
confidence: 99%
“…This explains why the follicular variant of PTC (FVPTC) has a very low frequency of microcalcifications (PBs) [ 69 ]. When FVPTC is infiltrative, the frequency of calcification can be higher but is rare in the encapsulated FVPTC [ 56 , 57 ]. Diffuse sclerosing variant of papillary thyroid carcinoma (DSVPTC) is an uncommon variant of PTC, characterized by diffuse involvement of one or both lobes of the thyroid gland [ 70 ].…”
Section: Calcification In Different Types Of Thyroid Cancermentioning
confidence: 99%